MANAJEMEN PENINGKATAN VALUE ADDED BUAH OKRA MENJADI PRODUK KHAS OLAHAN TEH DAN KOPI DI KBUPATEN JEMBER - Rahmandani, Muhammad Syafa'atur; Pangesti Mulyono, Resha Dwi Ayu; Fiba, Ivo Rajava; Rivieri, Yeremia; Hardikasari, Yunita; Kamiliah, Thiflatul (Program Studi Manajemen Institut Teknologi dan Bisnis Asia Malang, 2024)
The Okra plant is a herbal plant that contains various benefits and is one of the plants produced in large quantities in the Jember Regency area. One of the benefits of okra fruit is to prevent diabetes. However, even though it has various benefits, this fruit is often underestimated and is not even known by various groups in Jember or other areas. Therefore, this research is intended to improve the management of okra fruit so that it can provide high added value as a superior herbal product in Jember Regency. This research uses descriptive qualitative methods. The data used are primary and secondary data, as well as data collection techniques carried out by observation, interviews and literature reviews. The research results show that good management of okra fruit can make the fruit a processed herbal tea and coffee product which has a high selling price and is useful for health.